Microplastics Increase Soil pH and Decrease Microbial Activities as a Function of Microplastic Shape, Polymer Type, and Exposure Time - Zhao, Tingting; Lozano, Yudi M.; Rillig, Matthias C. (Frontiers in Environmental Science, 2021)
Microplastic pollution is a topic of increasing concern, especially since this issue was first addressed in soils. Results have so far been variable in terms of effects, suggesting that there is substantial context-dependency in microplastic effects in soil. To better define conditions that may affect microplastic-related impacts, we here examined effects as a function of microplastic shape and polymer type, and we tested if effects on soil properties and soil microbial activities change with incubation time. In our laboratory study, we evaluated twelve different secondary microplastics representing four microplastic shapes: fibers, films, foams and fragments; and eight polymer types: polyamide (PA), polycarbonate (PC), polyethylene (PE), polyester (PES), polyethylene terephthalate (PET), polypropylene (PP), polystyrene (PS), and polyurethane (PU). We mixed the microplastics with a sandy soil (0.4 % w/w) and incubated at 25 ℃ for 31 days. Then, we collected soil samples on the 3rd, 11th, and 31st day, and measured soil pH, respiration and four enzyme activities (acid phosphatase, β-D-glucosidase, cellobiosidase and N-acetyl-β-glucosaminidase). Our results showed that microplastics could affect soil pH, respiration and enzymatic activities depending on microplastic shape and polymer type, effects that were altered with incubation time. Soil pH increased with foams and fragments and overall decreased in the first days of incubation and then increased. Soil respiration increased with PE foams and was affected by the incubation time, declining over time. Overall, acid phosphatase activity was not affected by shape or polymer type. β-D-glucosidase activity decreased with foams, cellobiosidase activity decreased with fibers, films and foams while N-acetyl-β-glucosaminidase activities decreased with fibers and fragments. Enzymatic activities fluctuated during the incubation time, except N-acetyl-β-glucosaminidase, which showed a declining trend with incubation time. Enzymatic activities were negatively correlated with soil pH and this relationship was less strong when microplastics were added to the soil. Our study adds to the evidence that research should embrace the complexity and diversity of microplastics, highlighting the role of microplastic shape and polymer type in influencing effects; additionally, we show that incubation time is also a parameter to consider, as effects are dynamic even in the short term.